2016
DOI: 10.12714/egejfas.2016.33.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Spring bloom of the raphidophycean Heterosigma akashiwo in the Golden Horn Estuary at the northeast of Sea of Marmara

Abstract: Abstract:In the period of February-May 2012, harmful algal blooms (HABs) along with environmental factors were investigated biweekly in the Golden Horn Estuary at the northeast of the Sea of Marmara and a dense bloom of the raphidophyceaen Heterosigma akashiwo (Y.Hada) Y.Hada ex Y.Hara & M.Chihara was observed in late May. H. akashiwo abundance increased gradually from the lower estuary to the upper estuary. The dense bloom of H. akashiwo in late May occurred at the temperature of 20.2°C and salinity of 16.4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…During this study, the bloom of H. akashiwo occurred in the UE almost at the same time as that of the previous study. Results indicated that a rapid temperature rise in spring was the most important factor that caused a bloom of H. akashiwo , as reported by Dursun et al (2016). Nevertheless, high abundances were detected for diatoms Skeletonema marinoi and Thalassiosira sp., and the cryptophycean Plagioselmis prolonga , which are known to be bloom-forming species for the GHE (Tas et al , 2009; Tas & Yilmaz, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…During this study, the bloom of H. akashiwo occurred in the UE almost at the same time as that of the previous study. Results indicated that a rapid temperature rise in spring was the most important factor that caused a bloom of H. akashiwo , as reported by Dursun et al (2016). Nevertheless, high abundances were detected for diatoms Skeletonema marinoi and Thalassiosira sp., and the cryptophycean Plagioselmis prolonga , which are known to be bloom-forming species for the GHE (Tas et al , 2009; Tas & Yilmaz, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Algal blooms in the GHE have been discussed in detail by several studies (Tas et al , 2006, 2009; Tas & Okuş, 2011; Tas, 2015; Tas & Yilmaz, 2015; Dursun et al , 2016; Tas & Lundholm, 2016). Dense algal blooms, except for the raphidophycean Heterosigma akashiwo , were not recorded in the GHE during the study period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Harmful algal blooms (HABs) have usually been reported from the coasts of the northeastern Sea of Marmara and the Dardanelles. During the last decade, the diatom Pseudo-nitzschia calliantha, the dinoflagellates; Heterocapsa triquetra, Noctiluca scintillans, Prorocentrum micans, Prorocentrum cordatum and Scrippsiella acuminata (reported as Scrippsiella trochoidea) and the raphidophyte Heterosigma akashiwo have been reported as bloom-forming species (Turkoglu, 2008 andTas et al, 2009;Tas, 2015;Tas & Yilmaz, 2015;Dursun et al, 2016;Tas et al, 2016;Tas & Lundholm, 2017). In this study, we considered only the known potentially toxic species.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of phytoplankton composition have been performed in estuaries around the Mediterranean Sea (Trigueros & Orive, 2001; Burić et al ., 2007; Barbosa et al ., 2010). Recently, studies have focused on phytoplankton communities of the Golden Horn Estuary (GHE) by microscopic analysis including the variations in phytoplankton composition (Tas et al ., 2009; Dursun & Tas, 2019), planktonic diatom composition (Tas, 2017; Tas & Hernández-Becerril, 2017), and algal blooms and potentially harmful species (Tas & Okus, 2011; Tas, 2015, 2019; Tas & Yilmaz, 2015; Dursun et al ., 2016; Tas & Lundholm, 2017). However, no study has been performed in the GHE using HPLC, despite HPLC pigment signatures being widely used in Turkish seas (Ediger et al ., 2006; Eker-Develi et al ., 2012; Agirbas et al ., 2017; Yücel, 2017).…”
Section: Introductionmentioning
confidence: 99%